Optimization of a formula to develop iron-dense novel composite complementary flour with a reduced phytate/minerals molar ratio from dabi teff-field pea-based blends using a D-optimal mixture design - Tura, Diriba Chewaka; Belachew, Tefera; Tamiru, Dessalegn; Abate, Kalkidan Hassen (Frontiers in Nutrition, 2023)
Iron deficiency anemia is one of the major public health problems in children associated with inadequate intake of bioavailable iron. Thus, this research was aimed at incorporating dabi teff, the underutilized/forgotten crop into other pre-processed local food crops viz., germinated maize, roasted barley, roasted field pea, dehulled oats and linseed to develop optimized iron-dense novel composite complementary flour with reduced phytate/minerals molar ratio. Nutrisurvey software was employed to define ranges and they were constrained at 20-35% dabi teff, 0-30% field pea and 5-20% maize, while the rest were set constant at 25% barley, 15% oats and 5% linseed. Eleven experimental runs were generated from the six mixture components using Stat-Ease Design-Expert ® software version 11, D-optimal. Inductively Coupled Plasma-Optical Emission Spectrometry was used for the determination of micronutrients. 'Scheffe' regression was used to fit and test model adequacy and numerical multi-response optimization was performed using the Design-Expert ® to identify optimal points. Dabi teff contained a significantly higher (P <0.05) iron content at 86.5 mg/100g, iron density at 24.53 mg/100kcal and calcium content at 123.59 mg/100g. The new formulations contained significantly higher iron (3.31-4.36 times), iron density (3.25-4.27 times) and calcium (1.49 -1.58 times) as compared to the control flour and fulfilled FAO/WHO recommendations. The optimal formula was identified at 34.66% dabi teff, 25% barley, 15% oats, 15.34% field pea, 5% linseed and 5% maize flour ratios with response values at overall optimization to be 32.21 mg/100g iron, 77.51 mg/100g calcium, 2.59 mg/100g zinc, 0.233 phytate to iron molar ratio (Ph:Fe), 0.067 phytate to calcium molar ratio (Ph:Ca), 3.43 phytate to zinc molar ratio (Ph:Zn), and 6.63 phytate by calcium to zinc molar ratio (Ph*Ca:Zn) and it contained iron at 2.01 times higher than the standard, 4.44 times higher than the control and iron density at 8.47 mg/100kcal that was 4.39 times higher than the control. Thiese findings showed that optimized dabi teff-field pea based iron dense novel composite complementary flour with enhanced bioavailability can be developed and used as a sustainable food-based strategy to combat iron deficiency anemia among children in less developed countries like Ethiopia.